Youth and Adult Agrifood System Employment in Developing Regions: Rural (Peri-urban to Hinterland) vs. Urban. Issue 4 (3rd April 2021) - Dolislager, Michael; Reardon, Thomas; Arslan, Aslihan; Fox, Louise; Liverpool-Tasie, Saweda; Sauer, Christine; Tschirley, David L.
Abstract: Using a unique dataset covering 178, 794 households with 460, 654 individuals spanning Africa, Asia, and Latin America, we explore employment of youths across rural zones (peri-urban, intermediate, hinterland) and urban areas. Using full-time equivalents (FTEs), we compare own-farming versus farm-wage labour, and nonfarm wage- and self-employment. Nonfarm includes: (a) agrifood system (AFS) jobs post-farmgate, in food processing, wholesale, logistics, retail, and food service; (b) non-AFS. Key findings are noted in order by Africa, Asia, and Latin America (whose youth employment rates are 61%, 39%, and 48%). (1) AFS shares in FTEs of employed rural youths are substantial (21%, 21%, and 23%). Wage employment share of AFS is lower in Africa (25%) versus Asia and Latin America (75%). (2) Own-farming in FTEs of employed rural youths are higher in Africa (51%, 19%, and 12%). The share for adults in Africa is 36%. Regressions show youths' being in school does not reduce employment in own-farming (they are compatible), but reduces nonfarm labour. (3) Farm-wage employment shares in FTEs are small (4%, 13%, and 16%). (4) Regressions show that rural youths' being in a peri-urban area sharply increases AFS and non-AFS employment compared with hinterland youths who depend more on own-farming.